2017
DOI: 10.7150/ijbs.18404
|View full text |Cite
|
Sign up to set email alerts
|

Lycium Barbarum Polysaccharides Decrease Hyperglycemia-Aggravated Ischemic Brain Injury through Maintaining Mitochondrial Fission and Fusion Balance

Abstract: Although it has been reported that polysaccharides found in Lycium barbarum possess neuroprotective effects, little is known of their ability to ameliorate hyperglycemia-aggravated ischemia/reperfusion brain injury. In this study, normoglycemic (NG) and hyperglycemic (HG) rats were compared after 30 minutes of middle cerebral artery occlusion (MCAO), followed by 24 or 27 hours of reperfusion, with HG rats pretreated with lyceum barbarum polysaccharides (LBP) or insulin. In each group, the neurological deficit,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…Several investigations have shown that mitochondrial fission is critical for the mitochondrial homeostasis. Mitochondrial fission factor (MFF) or fission 1 (FIS1)-mediated excessive mitochondrial fission could lead to ROS burst and activation of the mitochondrial apoptosis pathway [39]. In the present study, we also found that MPS promoted MFF and FIS1 protein expressions while VO-OHpic attenuated these changes (Fig.…”
Section: Vo-ohpic Could Restore the Normal Mitochondrial Morphology supporting
confidence: 67%
“…Several investigations have shown that mitochondrial fission is critical for the mitochondrial homeostasis. Mitochondrial fission factor (MFF) or fission 1 (FIS1)-mediated excessive mitochondrial fission could lead to ROS burst and activation of the mitochondrial apoptosis pathway [39]. In the present study, we also found that MPS promoted MFF and FIS1 protein expressions while VO-OHpic attenuated these changes (Fig.…”
Section: Vo-ohpic Could Restore the Normal Mitochondrial Morphology supporting
confidence: 67%
“…LBP is the main active component of the Chinese wolfberry ( 21 ). LBP was purchased from Qinghai General Health Bio-science Co., LLC (Xining, China) and the purity of LBP was >50%.…”
Section: Methodsmentioning
confidence: 99%
“…Another study showed that Lycium barbarum derived from polysaccharides ameliorated hyperglycemia-aggravated ischemic/reperfusion brain injury through equilibrating mitochondrial fission and fusion. An increase in phospho-Drp1 and a decrease in Opa1 that negatively correlated with LBP dosage were observed [ 186 ]. In addition, according to Shi et al [ 187 ], Lycium barbarum polysaccharides protected against ischemic injury via modulating NR2B and NR2A signaling pathways.…”
Section: Polysaccharides and Healthmentioning
confidence: 99%